Crystallinity increases in semi crystalline polymers during high rate testing - Swallowe, G.M.; Fernandez, J.O.; Hamdan, S. (EDP Sciences, 1997)
During low rate deformation in tension semi-crystalline polymers can undergo a strain induced crystallisation during deformation which leads to increases in flow stress. This work extends studies of crystallinity in the polymers PEK, PEEK and PET to compression at high strain rates at a variety of temperatures. All three polymers show large increases in crystallinity when tested at high rates with PEK and PEEK showing increases only at rates of 103/s. It is speculated that the rapid increases in flow stress reported in polymers at high strain rates may be due to the rapidity of strain induced crystallisation at these strain rates.